Healthy diet social media campaign among Indonesian college students - Adella Adella; Elisabeth Rukmini (International Journal of Public Health Science (IJPHS), 2021)
Despite rise of self-perception towards eating balanced meals, obesity incidence remains high all over the world, reaching more than half billion people. It is worrisome since it leads to sedentary lifestyle that contributes to non-communicable diseases. Therefore, having adequate knowledge about healthy lifestyle, diet and eating habits from early age is crucial. Leveraging on the high usage of social media, educational intervention seems promising. In this study, we assess the impact of using social media campaigns through Instagram to raise knowledge and encourage behavioral changes. Both quantitative and qualitative analyses were performed. Freshmen (n=144) were selected as respondents and divided to two groups through random sampling. Those in intervention group received various information via Instagram for four months. All respondents had to fill self-administered knowledge questionnaires and food frequency questionnaire (FFQ) each month as evaluation. To evaluate the on-going campaign even more, we also collected qualitative data by interviewing respondents (n=14). Data were analysed using constant comparative method (CCM). By the end of campaign period, there was only positive increasing trend in knowledge. Instagram was perceived as a suitable campaign media despite needing improvements. Overall, Instagram educational intervention had only successfully raised awareness and knowledge, not students’ eating habits.